1999
DOI: 10.1038/sj.ejcn.1600860
|View full text |Cite
|
Sign up to set email alerts
|

Dietary habits affect the susceptibility of low‐density lipoprotein to oxidation

Abstract: Objective: To study, if there are differences in the fatty acid composition of low-density lipoprotein (LDL) in people eating three different long-standing habitual diets: vegetarian, high ®sh intake, or high saturated fat (milk fat) diet as a control group, and to study if these differences in¯uence the oxidation susceptibility of LDL. Design: Cross-sectional study using blood samples and a validated dietary frequency questionnaire with illustrations. Setting: Helsinki University Central Hospital, Finland. Su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 30 publications
(38 reference statements)
2
15
0
1
Order By: Relevance
“…Our previous study in subjects on a habitual fish diet (mean intake of fish 320 g/day), demonstrated a significantly higher oxidation susceptibility of LDL than in those on a diet containing about 30 g/day of fish (Korpela et al, 1999). A similar degree of oxidation susceptibility of LDL was observed in the nonsmoking fish group in our previous Table 3 LDL-related production of prostacyclin (measured as 6-keto-PGF 1a ) and cyclic AMP in endothelial cell culture during 24 h incubation (mean7s.e.m.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…Our previous study in subjects on a habitual fish diet (mean intake of fish 320 g/day), demonstrated a significantly higher oxidation susceptibility of LDL than in those on a diet containing about 30 g/day of fish (Korpela et al, 1999). A similar degree of oxidation susceptibility of LDL was observed in the nonsmoking fish group in our previous Table 3 LDL-related production of prostacyclin (measured as 6-keto-PGF 1a ) and cyclic AMP in endothelial cell culture during 24 h incubation (mean7s.e.m.…”
Section: Discussionmentioning
confidence: 88%
“…Some of native LDL samples were oxidized by CuSO 4 (10 mM) in order to get 45% and totally ox-LDL. The oxidation of LDL samples and the calculation of oxidation percentage were performed as described earlier (Korpela et al, 1999). The oxidation capacity curve was also measured in order to determine at which time point the oxidation should be stopped on the next oxidation process.…”
Section: Drugs and Chemicalsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to regulation for serum lipids (1,2), high serum levels of n-3 polyunsaturated fatty acids (3,4) and balance of n-3 and n-6 fatty acids (5,6) have a beneficial effect by preventing coronary heart disease through inhibition of platelet aggregation and lowering of blood pressure levels. In a series of studies, we reported that fish consumption increased the proportion of serum n-3 polyunsaturated fatty acids (7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%